A Review on the Economic Instability and Derivative Market of Pakistan - Perveen, Sadia; Ahmed, Masood; Begum, Rukhshinda (European Scientific Journal, ESJ, 2018)
This study covers the different problems of derivative market in Pakistan. Economic instability is the main constraint of derivative market in Pakistan. Due to instable economic conditions and restricted environment, corporate sector has not reflected significant participation in derivative market of Pakistan. Lack of infrastructure, political instability, ineffective governance, inexperience and unaware market participants are the other problems of Pakistan derivative market. Hence, literature is reviewed and analyzed due to unavailability of appropriate data for this study. Findings of the study have suggested that derivatives are an effective risk mitigating tool on one hand whereas on the other side, highly speculative activities in derivative market may be harmful for the financial markets and economic growth. In Pakistan perspective, all the players of financial market have adopted adequate risk mitigating strategies to avoid any adverse market scenario. Speculative activities are highly restricted due to economic instability as Pakistan is not in a position to absorb any financial shocks or crisis. The main regulatory authorities of this particular market are State Bank of Pakistan (SBP) and Security and Exchange Commission of Pakistan (SECP). These regulators are keenly observing market and taking necessary actions to prevent any adverse conditions. However, in developing economies these complex instruments create new risks which are badly affecting the whole economy.